Surviving the COVID-19 pandemic: The antecedents of success among European SMEs - Myint Moe Chit; Richard Croucher; Marian Rizov (European Management Review, 2023)
We research the antecedents of relative success among small and medium enterprises (SMEs) in avoiding temporary or permanent closure during the COVID-19 pandemic. We investigate the roles of firm-specific resources and state support policies in influencing SME fortunes, in a sizeable group of European countries covered in the World Bank Enterprise Survey. Using resource dependency, Varieties of Capitalism and Systems theories, we find that innovative capacities, institutional connectedness, governance, and management experience were major antecedents of success across all SMEs. Significant differences in outcomes were found between SMEs operating in old and new EU member states, and non-EU countries.
Keywords: 650; COVID-19; enterprise survival; government support; innovativeness; SMEs; World Bank Enterprise Survey